The relationship between the mtDNA copy number in insulin-dependent tissues and markers of endothelial dysfunction and inflammation in obese patients - Larisa Litvinova; Pavel Zatolokin; Maria Vulf; Ilia Mazunin; Daria Skuratovskaia (BMC, 2019)
Abstract Background Mitochondria play a central role in the regulation of energy metabolism, and the biogenesis of mitochondria is enhanced by the action of nitric oxide (NO), which is the key signaling molecule in the regulation of vascular homeostasis. A disturbance in the regulation of energy metabolism can be a key reason for the formation of insulin resistance and type 2 diabetes mellitus. Moreover, mitochondrial dysfunction leads to oxidative stress, which increases the production of proinflammatory cytokines. In this regard, the aim of this study was to identify the relationship of the copy number of mtDNA in adipose tissue from different locations (subcutaneous adipose tissue (SAT), mesentery (Mes), greater omentum (GO)), liver biopsy samples and mononuclear blood cells (MNCs) with endothelial dysfunction markers (eNOS, ET-1, iCAM-1, vCAM-1, VEGF) and inflammatory mediators (TNF-α, IL-6, IL-8, CRP, leptin) in obese patients (body mass index (BMI) > 35 kg/m2) with and without type 2 diabetes. Methods The study included 88 obese patients (BMI > 35 kg/m2) treated at the Kaliningrad Region Hospital. The control group consisted of 20 healthy donors. To measure mtDNA copy number we used droplet digital PCR. The concentrations of molecules (TNF-α, IL-6, IL-8, VEGF, eNOS, ET-1, iCAM-1, vCAM-1, VEGF) were measured in plasma using the following sandwich enzyme-linked immunosorbent assays (ELISAs). Quantitative determination of leptin was evaluated by flow-fluorimetry on a «Bio-Plex Protein Assay System». Statistical analysis and graphs were obtained in R Statistical Software (version 3.3.1). Results The systemic character of chronic subclinical inflammation in obesity is established, and an increase in the level of endothelial dysfunction molecules was observed in the blood plasma. The levels of TNF-a, IL-6, and IL-8 were positively correlated with increases in BMI, serum glucose and cholesterol levels. Conclusions The copy number of mtDNA in various fat stores was higher in obese patients with type 2 diabetes than in obese patients without diabetes or in the control subjects and was related to the levels of leptin and proinflammatory cytokines.